Variations in the mRNA expression of poly(ADP‐ribose) polymerases, poly(ADP‐ribose) glycohydrolase and ADP‐ribosylhydrolase 3 in breast tumors and impact on clinical outcome. Issue 12 (9th August 2013) - Bieche, Ivan; Pennaneach, Vincent; Driouch, Keltouma; Vacher, Sophie; Zaremba, Tomasz; Susini, Aurélie; Lidereau, Rosette; Hall, Janet
<x xml:space="preserve">Abstract</x> In order to assess the variation in expression of poly(ADP‐ribose) polymerase (PARP) family members and the hydrolases that degrade the poly(ADP‐ribose) polymers they generate and possible associations with classical pathological parameters, including long‐term outcome, the mRNA levels of PARP1, PARP2, PARP3, poly(ADP‐ribose) glycohydrolase (PARG) and ADP‐ribosylhydrolase 3 (ARH3) were examined using quantitative reverse transcription polymerase chain reaction in 443 unilateral invasive breast cancers and linked to hormonal status, tumor proliferation and clinical outcome. PARP1 mRNA levels were the highest among these five genes in both normal and tumor tissues, with a 2.45‐fold higher median level in tumors compared to normal tissues. Tumors (34.1%) showed PARP1 overexpression (>3 fold relative to normal breast tissues) compared to underexpression (<0.33 fold) in only 0.5%. This overexpression was seen in all breast tumor subgroups, with the highest fraction (51%) seen in the HR‐positive/ERBB2‐positive subgroup and was not highly associated with any other classical predictive factors. No correlation was seen between PARP1 mRNA and PARP‐1 protein levels in a subset of 31 tumors. PARP3 was underexpressed in 10.4% of tumors, more frequently in the HR‐negative tumors (25.4%) than the HR‐positive tumors (5.9%). This PARP3 underexpression was mutually exclusive with a PARP1 overexpression. PARP2 levels were unchanged between normal and tumor tissues and few tumors showed overexpression of PARG (3.8%) or ARH3 (3.4%). Within the subgroup of triple negative tumors, PARG mRNA levels below the median were associated with a higher risk of developing metastases (p = 0.039) raising the possibility this might be marker of clinical outcome.